Penerapan Asesmen Sumatif Berbasis Quizizz pada Materi Rukhsah - Pratama, Farandika Nanda; Shobirin, Muhammad; Irpandi, Fitra (ALSYS, 2025)
This study is motivated by the limited use of technology-based assessment media in Islamic Religious Education (Pendidikan Agama Islam/PAI), particularly on the topic of rukhsah, at SMP Negeri 1 Kudus. The aim of the research is to analyze the implementation of summative assessment using Quizizz to enhance student engagement and understanding of the material. A qualitative approach with a phenomenological design was employed, involving 27 students from Class 7H as subjects. Data were collected through observation, interviews, and documentation, and analyzed through data reduction, data presentation, and conclusion drawing. The findings show that the use of Quizizz as a digital summative assessment tool creates a competitive, enjoyable, and interactive learning environment. Features such as randomized questions, time limits, automated scoring, and appealing visual design were found to boost students’ motivation and participation in the assessment process. Feedback from both teachers and students indicated that ease of access and time efficiency are key advantages of the platform. Despite technical challenges such as limited devices and internet connectivity, Quizizz-based assessments remained effective when supported by proper technical planning. This study contributes to the development of digital summative assessments in PAI learning and recommends the expansion of formative and diagnostic assessments using similar platforms to foster a more adaptive, engaging, and meaningful learning experience in alignment with the Kurikulum Merdeka framework.